PENGARUH INTELLECTUAL CAPITAL, INVENTORY INTENSITY DAN MANAGERIAL OWNERSHIP TERHADAP EFFECTIVE TAX RATE (Studi Empiris pada Perusahaan Sektor Pertambangan yang Terdaftar di Bursa Efek Indonesia Tahun 2016-2020) - Sujarwo Sujarwo; Andri Sjahputra (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2022)
This study aims to empirically test and obtain evidence on the effect of intellectual capital, inventory intensity, and managerial ownership on effective tax rates. This study used samples of mining sector companies listed on the Indonesia Stock Exchange (BEI) in 2016-2020 with a population of 48 companies. The method of determining the sample was purposive sampling method obtained by 14 companies with a 5-year observation period obtained from 70 research data. This type of research is quantitative research. The analysis technique used is regression of panel data processed using Eviews software version 9. The results of this study show that in part (1) intellectual capital has a significant effect on effective tax rates, (2) inventory intensity has no significant effect on effective tax rates, and (3) managerial ownership has no significant effect on effective tax rates. Simultaneous intellectual capital, inventory intensity and managerial ownership have a significant impact on effective tax rates.